2010
DOI: 10.1007/s11165-009-9163-8
|View full text |Cite
|
Sign up to set email alerts
|

Is Pedagogical Content Knowledge (PCK) Necessary for Reformed Science Teaching?: Evidence from an Empirical Study

Abstract: This study tested a hypothesis that focused on whether or not teachers' pedagogical content knowledge (PCK) is a necessary body of knowledge for reformed science teaching. This study utilized a quantitative research method to investigate the correlation between a teacher's PCK level as measured by the PCK rubric (Park et al. 2008) and the degree to which his/her classroom is reform-oriented as measured by RTOP (Sawada et al. 2002). Data included 33 instructional sessions of photosynthesis and heredity videota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
86
0
26

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 180 publications
(114 citation statements)
references
References 34 publications
2
86
0
26
Order By: Relevance
“…Numerous researchers in the field of science education still use this work to organise research efforts or to design and carry out research studies (e.g., Baumert et al, 2010;Hashweh, 2005;Hill, Ball, & Schilling, 2008;Lee & Luft, 2008;Loughran, Mulhall, & Berry, 2008;Park, Jang, & Chen, 2010; F o r P e e r R e v i e w O n l y 4 pedagogical knowledge (PK). Over the past decade, many research projects have used these three main categories of teachers' professional knowledge to provide a theoretical background.…”
Section: Professional Knowledge Of Science Teachersmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous researchers in the field of science education still use this work to organise research efforts or to design and carry out research studies (e.g., Baumert et al, 2010;Hashweh, 2005;Hill, Ball, & Schilling, 2008;Lee & Luft, 2008;Loughran, Mulhall, & Berry, 2008;Park, Jang, & Chen, 2010; F o r P e e r R e v i e w O n l y 4 pedagogical knowledge (PK). Over the past decade, many research projects have used these three main categories of teachers' professional knowledge to provide a theoretical background.…”
Section: Professional Knowledge Of Science Teachersmentioning
confidence: 99%
“…Numerous researchers in the field of science education still use this work to organise research efforts or to design and carry out research studies (e.g., Baumert et al, 2010;Hashweh, 2005;Hill, Ball, & Schilling, 2008;Lee & Luft, 2008;Loughran, Mulhall, & Berry, 2008;Park, Jang, & Chen, 2010;Schmidt et al, 2007;Tatto et al, 2007;van Driel, Beijaard, & Verloop, 2001). For example, Baumert et al (2010) helped organise their evaluation of teachers' professional knowledge by using three categories: pedagogical content knowledge (PCK), content knowledge (CK) and pedagogical knowledge (PK).…”
Section: Professional Knowledge Of Science Teachersmentioning
confidence: 99%
“…Despite these findings, there is still no unified agreement among researchers on the best method or methods to assess PCK because of its complexity (Park, Jang, Chen, & Jung, 2011). The authors therefore found it necessary to analyze a multitude of studies from various STEM disciplines in order to construct viable instrumentation for investigating PCK in this study.…”
Section: Review Of Literaturementioning
confidence: 98%
“…Their rubric did not accurately reflect all essential elements of PCK nor did it provide much detail about the specific teaching of content and practices. Park et al (2011) developed a similar rubric that was used to rate teachers' PCK based on interview responses, lesson plans, and classroom observations. Like Loughran, Berry, and Mulhall (2007), they acknowledged that PCK is topic specific, but it…”
Section: Review Of Literaturementioning
confidence: 99%
See 1 more Smart Citation